An Exploration of Product and Process Innovation Practices in Mobile Coffee Shop Operations in Banda Aceh City: A Compliance Perspective on Sharia Law and Its Implications for Customer Satisfaction - Syarief Hidayat (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The rapid growth of mobile coffee shops in Indonesia, particularly in Banda Aceh, has intensified market competition. Within the context of Qanun Syariat Islam, business success depends not only on product quality but also on innovation and adherence to Islamic economic principles. This study aims to explore product and process innovation practices, compliance with Sharia economic law, and their implications for customer satisfaction. This research employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with mobile coffee shop owners and customers, as well as direct observations of business operations. Data were analyzed using thematic analysis, involving coding, categorization, and theme development. Validity was ensured through member checking and triangulation. Findings indicate that product innovation involves menu diversification, distinctive local flavors, and attractive packaging tailored to local preferences. Process innovation includes the adoption of digital cashier systems, cashless payments, and simplified service SOPs. Sharia compliance covers the use of halal-certified ingredients, transparent pricing, and ethical promotion. The integration of these three aspects fosters customer satisfaction that is both functional and value-based, thereby encouraging loyalty and positive word-of-mouth. These results confirm that competitive advantage in Banda Aceh’s mobile coffee shop sector can be built through a combination of innovation and Sharia-based values aligned with local culture. The findings expand the literature on differentiation strategies in halal-based culinary businesses.